(untitled) (Papeles, 2023)
In the present work we share questions, reflections and bets on the approach of Social Work in a historical key in professional training from the experience of a subject of the first year of the undergraduate degree in Social Work at the National University of Entre Ríos. We focus on the process of teaching and learning the stories of Social Work in a didactic-pedagogical proposal that implies a historical look at the disciplinary configuration, sharing different interpretations of its emergence and evolution. We understand that we are children of an era and from there builders of lived history. -history understood as past-present-future that finds us in the classrooms in a collective construction and interpretation. Thus, we organized the presentation with the title "the one from where we say about the history taught" as an introduction, then at first, we raised questions and problems that arise in the processes of teaching and learning the history of the profession. In a second moment, the journey that we have been carrying out in the subject in some analytical keys. At the end, without claiming conclusions but continuity of our reflection process, we outline premises, guidelines as local investigative processes that provide feedback to the training instances.